Influence of the Digital Environment on the Contemporary Worldview: Pro et Contra - Sergey V. Volodenkov; Sergey N. Fedorchenko; Nikolai M. Pechenkin (RUDN Journal of Political Science, 2023)
Global technological transformations of key areas of life of contemporary society, the formation and active functioning of global and national digital institutions that influence current socio-political processes, and the digitalization of social relations form a demand for comprehensive scientific research on the processes of digital influence on the development and functioning of modern social systems. This article is aimed at considering the problem of the relationship between digital and worldview aspects of the functioning of modern societies. In connection with this, the research issue was to determine the degree and nature of the influence of digitalization processes, as well as directly the digital environment and institutions on the content aspects of the individual’s worldview. This research question is directly related to the study of the phenomenon of public consent in the context of the formation of digital polymentality. To answer the research question posed in the paper, the authors conducted a discourse analysis of the existing scientific literature on the relationship between digitalization and worldview in the pro et contra logic. An international expert study was also conducted, which made it possible to identify the main expert positions on the study, as well as the key risks, threats, and challenges in the field of preserving the traditional worldview and achieving public consent based on the unity of value-semantic and worldview ideas of individuals. The main conclusion of the paper is the fundamental ambiguity of the positions of scientists and experts, justified by the results of the study, in assessing the degree and nature of the influence of digitalization, the digital environment and institutions on the content parameters of the worldview of a modern person, as well as the ambiguity of the value-semantic attitudes formed and maintained in the digital environment.